Profile of Anemia with special reference to hemoglobinopathies in a tertiary care centre in Madhya Pradesh - Dr Jyoti Sanghvi; Dr Ajit Asati (Pediatric Review: International Journal of Pediatric Research, 2015)
Introduction: Haemoglobinopathies constitute very important causative factors for anemia of childhood, especially in those regions where abnormal hemoglobin genes are highly prevalent. Thalassemia and Sickle cell anemia can be prevented by proper genetic counseling and screening. Material Methods: This cross-sectional one year study was conducted at Sri Aurobindo hospital Indore in department of pediatrics with the primary objective is to find out clinical and hematological characteristics of anemia with special reference to hemoglobinopathy. A total of 100 subjects were included. Results: The mean age of patients was 4.63 ± 4.18 years. Prevalence of Iron deficiency anemia was 61%, Vitamin B12 deficiency was 12%, thalassemia trait 10%, sickle cell anemia 10% and thalassemia major was 7%. , Mean Hb concentration was 6.54±1.63 g/dl and the MCV values ranged between 59.2±5.8 and 100.7±13.9. Mean reticulocyte was found 3.85±2.11 in thalassemia major, 4.0±2.10 and4.6±2.5 in sickle cell anemia. Mean HbA2 level was 2.45±0.69, in thalassemia major, 5.13±0.61 in thalassemia trait, and 2.01±0.71 in sickle homozygous. Mean HbF level was 92.57±1.6 in thalassemia major, 2.15±1.24 in thalassemia trait and 20.2± 9.6 in sickle cell anemia. Conclusion: HPLC is a reliable method for screening of thalassemia.Screening should be done among all suspected patients to find out the exact prevalence of thalassemia. Treatment should be started as soon as thalassemia positive is detected before the end organ damage has occurred. Genetic counseling of the patient’s family for next pregnancy should be done to avoid birth of a thalassemia child in their family.